2015
DOI: 10.1038/leu.2015.358
|View full text |Cite
|
Sign up to set email alerts
|

Dnmt3a regulates myeloproliferation and liver-specific expansion of hematopoietic stem and progenitor cells

Abstract: DNMT3A mutations are observed in myeloid malignancies, including myeloproliferative neoplasms (MPN), myelodysplastic syndromes (MDS), and acute myeloid leukemia (AML). Transplantation studies have elucidated an important role for Dnmt3a in stem cell self-renewal and in myeloid differentiation. Here we investigated the impact of conditional hematopoietic Dnmt3a loss on disease phenotype in primary mice. Mx1-Cre-mediated Dnmt3a ablation led to the development of a lethal, fully penetrant myeloproliferative neopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 51 publications
9
51
0
Order By: Relevance
“…Considering that most of the reported DNMT3A mutations in human myeloid neoplasms are heterozygous (1, 2), we observed a transplantable AML phenotype in Dnmt3a R878H/WT heterozygous animals whereas homozygous mice showed growth inhibition and died soon after birth. The leukemia phenotype in mice bore some similarities to that in a Dnmt3a −/− murine model (23). Our results showed that leukemic LSKs were composed mostly of LRPs and contained leukemia-initiating cells.…”
Section: Discussionsupporting
confidence: 53%
“…Considering that most of the reported DNMT3A mutations in human myeloid neoplasms are heterozygous (1, 2), we observed a transplantable AML phenotype in Dnmt3a R878H/WT heterozygous animals whereas homozygous mice showed growth inhibition and died soon after birth. The leukemia phenotype in mice bore some similarities to that in a Dnmt3a −/− murine model (23). Our results showed that leukemic LSKs were composed mostly of LRPs and contained leukemia-initiating cells.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, analysis of all expressed genes failed to demonstrate any trends in expression that correlated with differences in methylation in promoters or gene bodies (Figures 5E, S5J). Importantly, specific genes previously reported to be dysregulated by the overexpression of DNMT3A R882H and/or the loss of Dnmt3a in mice (Guryanova et al, 2016; Jeong et al, 2013; Rau et al, 2016) were not different between the primary human DNMT3A R882H/C and DNMT3A WT AMLs in this study, or in the TCGA dataset (Figures 5F, S5K), demonstrating that DNMT3A R882H/C AMLs do not have an easy-to-define expression phenotype, despite the presence of significant differences in methylation at some linked promoters.…”
Section: Resultsmentioning
confidence: 99%
“…Jankowska et al reported that 25% of patients with sAML arising from previous CMML harbored DNMT3A mutations, possibly suggesting a higher probability of evolution to AML for CMML patients with DNTM3A mutations; however, this study investigated a small cohort (Jankowska et al 2011) and larger studies are needed. As described for AML, DNMT3A mut CMML is reported to display significantly reduced DNA methylation, mainly at intergenic and intronic regions (Meldi et al 2015) and low-DNA methylation levels are also reported in a Dnmt3a-null MDS/ MPN mouse model (Guryanova et al 2015). However, whether this methylation pattern impacts the disease phenotype and eventually the prognosis of MDS/MPN patients is still unknown, and more studies are required to answer these important questions.…”
Section: Dnmt3a Mutations In Myeloproliferative Neoplasms and Myelodymentioning
confidence: 93%